Analisis Faktor-Faktor yang Mempengaruhi Tingkat Pengungkapan Risiko dalam Laporan Tahunan Perusahaan Perbankan di Indonesia Tahun 2017 - kiafe, Siti Fathia B1031141050 (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2019)
The objective for this study is to examine the factors that influencing the level of risk disclosure such as audit committee, independence board of comissioners, managerial ownership, institusional ownership, company size, external auditor quality and financial performance. Content analysis is used to collect and analyze data of forty two annual reports from Indonesian Banking Companies in year 2017. The results indicates that audit committee, independence board of comissioners, managerial ownership, company size and financial performance didnâ€™t have relationship with the level of risk disclosure. Nevertheless, institusional ownership and external auditor quality have positively affect the level of companies risk disclosure. Achmad, T., Faisal , F., & Oktarina, M. (2017). Factors Influencing Voluntary Corporate Risk Disclosure Practices by Indonesian Companies. Corporate Ownership & Control, 14(3).Adamu , M. U. (2013). Risk Reporting: A Study of Risk Disclosures in the Annual Reports of Listed Companies in Nigeria. Research Journal of Finance and Accounting, 4(16), 140-147.Aljifri, K., & Hussainey, K. (2007). The Determinants of Forward-looking Information in Annual Reports of UAE Companies. Managerial Auditing Journal, 22(9), 881-894.Al-Maghzom, A., Hussainey, K., & Aly, D. (2016). Corporate Governance and Risk Disclosure Evidence from Saudi Arabia. Corporate Ownership and Control Journal, 13(2), 145-166.Al-Maghzom, A., Hussainey, K., & Aly, D. (2016). The Level of Risk Disclosure in Listed Banks Evidence from Saudi Arabia. Corporate Ownership & Control, 14(1), 175-194.Al-Moataz, E., & Hussainey, K. (2013). Determinants of Corporate Governance Disclosure in Saudi Companies. Journal of King Abdulaziz University: Economics and Administration, 27(2), 411-430.Al-Shammari, B. (2014). Kuwait Corporate Characteristics and Level of Risk Disclosure: A Content Analysis Approach. Journal of Contemporary Issues in Business Research, 3(3), 128-153.Amran, A., & Che Haat, M. H. (2009). Risk reporting: An exploratory study on risk management disclosure in Malaysian annual reports. Managerial Auditing Journal, 24(1), 39-57.Anisa, W. G., & Prastiwi, A. (2012). Analisis Faktor yang Mempengaruhi Pengungkapan Manajemen Risiko. Dipetik Agustus 14, 2018, dari Diponegoro University Institusional Repository: http://eprints.undip.ac.id/35288/Ansah, S. O. (1998). The Impact of Corporate Attributes on the Extent of Mandatory Disclosure and Reporting by Listed Companies in Zimbabwe. The International Journal of Accounting, 33(5), 605-631.Aryani, D. N. (2016, Februari). The Determinants and Value Relevance of Risk Disclosure in The Indonesian Banking Sector. Disertasi. United Kingdom: University of Gloucestershire. Dipetik Agustus 26, 2018, dari http://eprints.glos.ac.uk/3429/Â Ashfaq, K., Zhang, R., Munaim, A., & Razzaq, N. (2016). An Investigation into the Determinants of Risk Disclosure in Banks: Evidence from Financial Sector of Pakistan. International Journal of Economics and Financial Issues, 6(3), 1049-1058.Atanasovski, A., Serafimoska, M., Jovanovski, K., & Jovevski, D. (2015). Risk Disclosure Practices in Annual Reports of Listed Companies: Evidence from a Developing Country. Research Journal of Finance and Accounting, 6(1), 184-192.Barakat, A., & Hussainey, K. (2013). Bank governance, regulation, supervision, and risk reporting: Evidence from operational risk disclosures in European banks. International Review of Financial Analysis, 30, 254â€“273.Barako, D. G., Hancock, P., & Izan, H. Y. (2006). Factors Influencing Voluntary Corporate Disclosure by Kenyan Companies. Journal compilation, 4(2), 107-125.Beretta, S., & Bozzolan, S. (2004). A framework for the analysis of firm risk communication. The International Journal of Accounting, 39, 265â€“ 288.Brown, A. (2015). Financial Risk Management For Dummies. John Wiley & Sons.Darmadi, S. (2013). Corporate governance disclosure in the annual report: An exploratory study on Indonesian Islamic banks. Humanomics, 29(1), 4-23.Elshandidy, T., & Neri, L. (2014). Corporate Governance, Risk Disclosure Practices, and Market Liquidity: Comparative Evidence from the UK and Italy. Corporate Governance: An International Review, 23(4).Elshandidy, T., Fraser, I., & Hussainey, K. (2013). Aggregated, voluntary and mandatory risk disclosure incentives: Evidence from UK FTSE all share companies. International Review of Financial Analysis, 30, 320-333.Elzahar, H., & Hussainey, K. (2012). Determinants of Narrative Risk Disclosures in UK Interim Reports. THE JOURNAL OF RISK FINANCE, 13(2), 133-147.Fathi, J. (2013). Corporate Governance and the Level of Financial Disclosure by Tunisian Firm. Journal of Business Studies Quarterly, 4(3).Ghozali, I. (2013). Aplikasi Analisis Multivariate dengan Program IBM SPSS 21 (Vol. 7). Semarang: Badan Penerbit Universitas Diponegoro.Habtoor, O. S., Ahmad, N., Mohamad, R. N., & Che Haat, M. H. (2017). Linking Corporate Risk Disclosure Practices with Firm-Specific Characteristics in Saudi Arabia. Gadjah Mada International Journal of Business, 19(3), 247-266.Hassan, M. K. (2008). The level of corporate risk disclosure in UAE. Proceedings of the British Accounting Association conference. Blackpool.Hassan, M. K. (2009). UAE corporations-specific characteristics and level of risk disclosure. Managerial Auditing Journal, 24(7), 668-687.Hassan, O. G., Giorgioni, G., & Romilly, P. (2006). The extent of financial disclosure and its determinants in an emerging capital market: the case of Egypt. International Journal Accounting, Auditing and Performance Evaluation, 3(1), 41-67.Healy, P. M., & Palepu, K. G. (2001). A review of the empirical disclosure literature: discussion. Dalam J. E. Core (Penyunt.), JAE Conference. 31, hal. 441-456. ScienceDirect.Hossain, M. (2008). The Extent of Disclosure in Annual Reports of Banking Companies The Case of India. European Journal of Scientific Research, 23(4), 659-680.Iatridis, G. (2008). Accounting disclosure and firms' financial attributes: Evidence from the UK stock market. International Review of Financial Analysis, 17, 219â€“241.ICAEW.Â  No surprises: Working for better risk reporting. Dipetik September 18, 2018, dari The Institute of Chartered Accountants in England & Wales: https://www.icaew.com/-/media/corporate/files/technical/research-and-academics/publications-and-projects/financial-reporting-publications/briefing-06-02-no-surprises.ashxJensen, M. C., & Meckling, W. H. (1998). Theory of the Firm: Managerial Behavior, Agency Costs and Ownership Structure. Journal of Financial Economics, 3(4), 305-360.Kasmir. (2017). Analisis Laporan Keuangan (Vol. 10). Jakarta: Raja Grafindo Persada.Khlif, H., & Hussainey, K. (2016). The association between risk disclosure and firm characteristics: a meta-analysis. Journal of Risk Research, 19(2), 181-211.Korczak, A. (2004). Managerial Ownership and Informativeness of Accounting Numbers in a European Emerging Market. Dipetik September 12, 2018, dari SSRN: https://papers.ssrn.com/sol3/papers.cfm?abstract_id=495123Kusumaningrum, R. A., & Chariri, A. (2013). Pengaruh Kepemilikan Institusional dan Karakteristik Dewan Komisaris Terhadap Pengungkapan Manajemen Risiko. Diponegoro Journal Of Accounting, 2(4), 1-15.Linsley, P. M., & Shrives, P. J. (2000). Risk management and reporting risk in the UK. Dipetik September 3, 2018, dari Research Gate: https://www.researchgate.net/profile/Philip_Linsley/publication/266016884_Risk_management_and_reporting_risk_in_the_UK/links/55af71be08ae1bc0454ab812/Risk-management-and-reporting-risk-in-the-UK.pdfLinsley, P. M., & Shrives, P. J. (2005). Examining Risk Reporting in UK. The Journal of Risk Finance, 6(4), 292-305.Mgammal, M. H. (2017). The Effect of Ownership Structure on Voluntary Disclosure: Evidence from Saudi Arabia. Journal of Advanced Management Science, 5(2), 138-151.Miihkinen, A. (2012). What Drives Quality of Firm Risk Disclosure? The Impact of a National Disclosure Standard and Reporting Incentives under IFRS. The International Journal of Accounting, 47(4), 437-468.Mokhtar, E. S., & Mellet, H. (2013). Competition, corporate governance, ownership structure and risk reporting. Managerial Auditing Journal, 28(9), 838-865.Nahar, S. (2015, Juni). Risk disclosure practices: their determinants and association with bank performance. Disertasi. Australia: Swinburne University of Technology. Dipetik September 8, 2018, dari https://researchbank.swinburne.edu.au/items/5329fa96-76b9-4dfa-8408-d1a53667458d/1/Nahar, S., Azim , M., & Jubb, C. (2016). The determinants of risk disclosure by banking institutions Evidence from Bangladesh. Asian Review of Accounting, 24(4), 426-444.Naveed, F., Khurshid, M. K., & Shakeel, M. (2015). Factors Affecting the Corporate Governance Disclosure: An Analysis of Manufacturing Firms of Pakistan. European Journal of Business and Management, 7(22), 12-20.Ntim, C. G., Lindop, S., & Thomas, D. A. (2013). Corporate Governance and Risk Reporting in South Africa: A Study of Corporate Risk Disclosures in the Pre- and Post-2007/2008 Global Financial Crisis Period. International Review of Financial Analysis, 30, 363-383.Oktarina, M. (2015). Analisis Pengaruh Karakteristik Perusahaan Terhadap Pengungkapan Risiko pada Perusahaan-Perusahaan yang Listing di Bei Tahun 2013. Skripsi. Dipetik September 19, 2018, dari Diponegoro University Institutional Repository: http://eprints.undip.ac.id/46154/Oliveira, J., Rodrigues, L. L., & Craig, R. (2011). Risk-related disclosure practices in the annual reports of Portuguese credit institutions: an exploratory study. Journal of Banking Regulation, 12(2), 100â€“118.Oliveira, J., Rodrigues, L. L., & Craig, R. (2011). Riskâ€related disclosures by nonâ€finance companies: Portuguese practices and disclosure characteristics. Managerial Auditing Journal, 26(9), 817-839.Otoritas Jasa Keuangan. (2018, September 4). Diambil kembali dari Otoritas Jasa Keuangan: https://www.ojk.go.id/id/Default.aspxPedoman Penerapan Manajemen Risiko Berbasis Governance. (2012). Dipetik September 4, 2018, dari Komite Nasional Kebijakan Governance: http://www.knkg-indonesia.org/dokumen/Pedoman-Manajemen-Risiko-Berbasis-GCG.pdfProbohudono, A. N. (2012, September). A Comparative Analysis of Voluntary Risk Disclosures. Disertasi. Perth, Australia: Curtin University. Dipetik September 5, 2018, dari http://hdl.handle.net/20.500.11937/2132Probohudono, A. N., Tower, G., & Rusmin, R. (2013). Diversity in Risk Communication. Australasian Accounting, Business and Finance, 7(1), 41-58.Puspitaningrum, D., & Atmini, S. (2012). Corporate governance mechanism and the level of internet financial reporting: Evidence from Indonesian companies. Procedia Economics and Finance, 2, 157 â€“ 166.Solomon, J. F., Solomon, A., Norton, S. D., & Joseph, N. L. (2000). A Conceptual Framework for Corporate Risk Disclosure Emerging from The Agenda for Corporate Governance Reform. British Accounting Review, 32, 447-478. doi:doi:10.1006/bare.2000.0145Suhardjanto, D., Dewi, A., Rahmawati, E., & M, F. (2012). Peran Corporate Governance dalam Praktik Risk Disclosure pada Perbankan Indonesia. Jurnal Akuntansi dan Auditing, 9(1), 16-30.Sulistyaningsih, & Gunawan, B. (2016). Analisis Faktor-Faktor yang Memengaruhi Risk Management Disclosure. Riset Akuntansi dan Keuangan Indonesia, 1.Wachira, M. (2018). Determinants of risk disclosures in Kenyan. African Journal of Business Management, 12(10), 267-273.Â